Analysis of Switching Behavior of Buy Now Pay Later Product Users Using Push Pull Mooring Framework: Analisis Switching Behavior Pengguna Produk Buy Now Pay Later Menggunakan Push Pull Mooring Framework - Yuliyanti, Tiara; Champaca, Mychelia (Fakultas Ekonomi Universitas Kadiri, 2024)
The objective of this research is to identify the impacts of privacy concern as a push effect, monetary rewards of alternative as a pull effect, and inertia as a mooring effect on product switching behavior in buy now pay later among SPaylater users in Jabodetabek. The respondents of this quantitative study were selected through purposive sampling, and the data was analyzed using SEM-PLS (Structural Equation Modeling – Partial Least Squares). The results of the assessment lead to conclusions that privacy concern as a push effect positively and significantly influences the switching behavior, that monetary rewards of alternative as a pull effect positively and significantly influences the switching behavior, and that inertia as a mooring effect has no effect on the switching behavior. Further, the results also indicate that inertia is not significant in moderating the impact of privacy concern on the switching behavior and the impact of monetary rewards of alternatives on the switching behavior. In addition this study finds factors that make individuals switch to other paylater services based on migrating or switching theory as well as consumer’s decision-making processes based on the studied variables